Database Consistency Improvement In Job Offering System Using Normalization Method - Fahrir Rijal Fahmi Maulana; Febriliyan Samopa (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
The role of information systems in modern life today is very important, especially in a company to make strategic decisions or actions. Information systems must be free from data anomalies. Data anomalies can occur due to poor database structure design. This happens in job offering systems that still have data anomalies. This study uses the normalization method to verify the quality of the database in the job offering system. Normalization is a technique that focuses on grouping several attributes into an entity based on certain criteria to achieve normal form. Normalization aims to maintain data consistency and integrity. The job offering information system has two databases to carry out all its functions. The first database is for the needs of processing job offering information system data. The second database is for the needs of processing company organizational structure data. This study has identified both databases of the job offering system. There are 2 violations of the normalization provisions found. Violations occur in the employee and schedule_wwc tables which do not follow the 3NF normalization provisions. Improvements need to be made to the database to improve data consistency in the job offering system. This study has made improvements by modeling data according to the data needs of the job vacancy information system. The modeling produces a conceptual data model (CDM), a logical data model (LDM) and a physical data model (PDM). The modeling results have been reverified using the normalization method and are free from any violations.